2022
DOI: 10.1155/2022/2476493
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside R1 Facilitated Wound Healing in High-Fat Diet/Streptozotocin-Induced Diabetic Rats

Abstract: Diabetic ulcers bring about high morbidity and mortality in patients and cause a great economic burden to society as a whole. Since existing treatments cannot fulfil patient requirements, it is urgent to find effective therapies. In this study, the wound healing effect of topical notoginsenoside R1 (NR1) treatment on diabetic full-thickness wounds in type II diabetes mellitus (T2DM) was induced by the combination of a high-fat diet and streptozotocin (STZ) injection. NR1 significantly increased the wound closu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…An interaction of AA with MMP-2 better than their natural inhibitor was also demonstrated in an in-silico study [32]. Other natural compounds such as quercetin, luteolin, vicenin-2, and notoginsenoside R1 have been associated with the downregulation of MMP-9, TNFα, IL1β, and IL6, and upregulation of antioxidant enzymes, TIMP, IL10, VEGF, TGFb1, on streptozotocin-induced diabetic rats [33][34][35]. For MMP-13 (which have essential roles in the turnover of the collagen matrix of bone) natural compounds such as curcumin, resveratrol, and epigallocatechin-3-gallate inhibit the IL-1β or advanced glycation end products-induced production of MMP-13, IL6 or TNFα by chondrocytes [36,37].…”
Section: Molecular Dynamics Between Pdms Inhibitors and Mmp-3 Mmp-13 ...mentioning
confidence: 65%
“…An interaction of AA with MMP-2 better than their natural inhibitor was also demonstrated in an in-silico study [32]. Other natural compounds such as quercetin, luteolin, vicenin-2, and notoginsenoside R1 have been associated with the downregulation of MMP-9, TNFα, IL1β, and IL6, and upregulation of antioxidant enzymes, TIMP, IL10, VEGF, TGFb1, on streptozotocin-induced diabetic rats [33][34][35]. For MMP-13 (which have essential roles in the turnover of the collagen matrix of bone) natural compounds such as curcumin, resveratrol, and epigallocatechin-3-gallate inhibit the IL-1β or advanced glycation end products-induced production of MMP-13, IL6 or TNFα by chondrocytes [36,37].…”
Section: Molecular Dynamics Between Pdms Inhibitors and Mmp-3 Mmp-13 ...mentioning
confidence: 65%
“…More importantly, NR1 administration gives rise to the down-regulation of MMP-9, MMP-3, IL-1b, and IL-6, while up-regulation of TIMP1 as well as TGF-b1. The results of RNA-Seq technology illustrate that NR1 mainly influence ECM related processes and inflammation in diabetic wound healing by targeting TIMP-1 and MMP-3 (93). Thus, these phenomena indicate that NR1 may be a feasible candidate agent for diabetic ulcer via regulating MMP-mediated signaling pathway.…”
Section: Steroids and Terpenoidsmentioning
confidence: 92%
“…In recent times, a variety of active compounds have been isolated and identified from PZH increasingly (Li et al, 2022b). Recently reported compounds are notoginsenoside (Cao et al, 2022), ginsenosides (Ramli et al, 2022), taurine (McGurk et al, 2022, citric acid and malic acid (Słupski et al, 2022), muscone (Fu et al, 2016) etc., which have been demonstrated to exhibit antioxidant, antiinflammatory, and anti-tumor effects (Huang et al, 2019). It has been reported that PZH perhaps heals a wide range of liver injuries and inflammation (Fu et al, 2016;Qi et al, 2017;Li et al, 2018;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%